A fixation guide for the accurate insertion of fibular segments in mandibular reconstruction. (June 2017) - Numajiri, Toshiaki; Tsujiko, Shoko; Morita, Daiki; Nakamura, Hiroko; Sowa, Yoshihiro
Abstract: Background: Computer-aided design and computer-assisted manufacturing (CAD/CAM) of cutting guides are now being used in mandibular reconstruction with fibular bone flaps. Improvements in guide design and accuracy are needed to increase the benefits to patients. Cutting guides have become popular, but fixation guides are rarely considered. Materials and methods: The aim of this study was to determine whether using a fixation guide would contribute to better accuracy in mandibular reconstruction. Mandibular segmental osteotomies and fibular reconstructions were performed using model surgery. Models were divided into two groups: without or with a fixation guide (n = 13 for each group). After reconstruction, the distances between reference points such as the condylion laterale (Cl), gonion, and mental tubercle (T) were measured and compared with those of the preoperative virtual plan. Deviations in final positions between the two groups were analyzed. Results: The mean deviations were 2.61 mm (range 0.05–7.65 mm) and 2.05 mm (range 0.07–8.52 mm) in the groups without and with a fixation guide, respectively. The overall results were significantly better when a fixation guide was used (p = 0.03). Distances including the Cl reference points such as ClCl (p = 0.02) and Cl–T (p = 0.001) were particularly improved. Conclusions: Using a fixation guide together with a cutting guide makes mandibular reconstruction more accurate, particularly for positioning the Cl reference points. Therefore, when a CAD/CAM-produced cutting guide is used in preparation for surgery, it is recommended to use a fixation guide as well for more accuracy.